The iconic Hector Pieterson photo and the power of adaptations - Ewald Mengel (Tydskrif vir Letterkunde, 2019)
In South Africa, the iconic Hector Pieterson photo is the starting point for many artists to deal with their own personal trauma and the communal trauma of their nation. The iconicity of this photo has sparked many different adaptations in various fields of art. Considering that we are talking about a traumatized country, Freud’s concept of “repetition compulsion” seems to be one explanation for this phenomenon. However, art is only seldom a mere product of traumatization. Quayson’s concept of “symbolization compulsions” comes closer to explaining the phenomenon of repetition in the arts, because it leaves the artists more freedom of expression and does not suggest that art is the result of illness, while still implying ‘compulsion’ and ‘obsession’ in the act of creation. I want to suggest that ‘repetition’ in the arts in the South African context is not so much a sign of confinement and restriction, but that the many adaptations of the unique historical incident should rather be understood as attempts of ‘working through’ collective trauma, making sense of history, and contributing to the country’s healing.